Calculation of Partial Charges on Functional Groups in Organic Compounds - Sekhon, B.S. (Asian Journal of Chemistry, 2010)
The principle of electronegativity equalization has been applied for the calculation of group partial charge on functional groups in organic compounds. The increasing alkyl chain length increased partial negative charge on groups such as OH, COOH, CONH2, COCl,OC(O)CH3, OC2H5, NH2, CHO and Cl. The partial negative charge on various groups decrease in the order: acid chloride > ester > amide > aldehyde > chloro > alcohol > ether > amine for each alkyl group. The reactivity of organic compounds is correlated with the partial charge on functional group.